Islamic Education Actualization in The Family Environment During The Covid 19 Pandemic - Bobi Erno Rusadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
During the Covid 19 pandemic, this is an opportunity for every parent to build closeness and instill the values of Islamic education in their children. Routine work that is usually carried out in the office, transferred to home or work from home. Parents' activities at home should be used to actualize Islamic education that parents have neglected or have not implemented. This study aims to describe the actualization of Islamic education carried out by parents in the family environment during the pandemic. The research method used is qualitative. The data collection method using questionnaires and interviews. This research is focused on three scopes of Islamic education, namely faith education, worship education, and moral education. The results of the study are that in actualizing Islamic education in the family environment there are several activities carried out by parents. To actualize Islamic education in the aspect of faith education, parents carry out several activities, namely dialogue, instilling a muraqabah attitude, getting used to thayyibah sentences, telling stories of friends, and seeing the universe. In the aspect of worship education, the activities carried out are inviting children to read the Qur'an, inviting children to pray 5 times a day on time, getting used to giving alms, and setting an example. While in the aspect of moral education, the activities carried out by parents are getting children to say greetings, getting children to speak politely, reprimanding and giving advice when children say dirty words, and getting children to eat with good eating manners, and providing examples